Upregulation of Small Ubiquitin-Like Modifier 2 and Protein SUMOylation as a Cardioprotective Mechanism Against Myocardial Ischemia-Reperfusion Injury - Zhao, Wei; Zhao, Jia; Zhang, Xiuying; Fan, Ni; Rong, Jianhui (Frontiers in Pharmacology, 2021)
Background: Small ubiquitin-like modifier (SUMO) proteins modify proteins through SUMOylation as an essential protein post-translational modification (PTM) for regulating redox status, inflammation, and cardiac fibrosis in myocardial infarction. This study aimed to investigate whether natural product puerarin could alleviate myocardial ischemia/reperfusion injury (MI-RI) by targeting protein SUMOylation. Methods: Mouse MI-RI model was induced by ligating the left anterior descending (LAD) coronary artery and subsequently treated with puerarin at the dose of 100 mg/kg. Rat cardiomyocyte H9c2 cells were challenged by hypoxia/reoxygenation and treated with puerarin at concentrations of 10, 20, and 40 μM. The infarction area of mouse hearts was assessed by 2% TTC staining. Cell damage was analyzed for the release of lactate dehydrogenase (LDH) in serum and cell culture medium. Western blot technique was employed to detect the expression of SUMO2, phospho-ERK, pro-inflammatory biomarker COX2, fibrosis index galectin-3, apoptosis-related protein cleaved PARP-1. The activation of the estrogen receptor (ER) pathway was assayed by the dual-luciferase reporter system. Results: The present study validated that puerarin effectively reduced myocardial infarct size and LDH release in the mouse MI-RI model. In the cell culture system, puerarin effectively decreased the release of LDH and the protein level of COX2, galectin-3, and cleaved PARP-1. Mechanistic studies revealed that puerarin increased the expression of SUMO2, SUMOylation of proteins and the activation of ER/ERK pathway in cardiomyocytes. ER, ERK and SUMO2 inhibitors attenuated the cardioprotective effects of puerarin. Conclusion: Puerarin may alleviate myocardial injury by promoting protein SUMOylation through ER/ERK/SUMO2-dependent mechanism.